2020
DOI: 10.37256/ges.112020146.12-22
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Adult Classic Theatre Audiences’ Perceptions and Behaviour

Abstract: Many cultural institutions are experiencing challenges to implement different types of market-oriented behaviour in order to ensure their existence. Classic theatres are faced with many challenges related to their audience. One of the challenges is related to traditional audience that is declining and ageing. The aim of this research was to identify and analyse the key factors that contribute to understanding of attitudes and behaviour of 35+ theatre audiences in order to suggest appropriate marketing strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…They found that older audiences (over 60) in the Czech Republic are the most frequent classic theatre attendees. The same situation exists in Croatia, and if this is related to the longterm trend of the decline of classic theatre audiences (Leko Šimić & Pap, 2020), it is clear that a detailed age segments analysis is needed. Moreover, although several newer studies have concentrated on motivational factors (Walmsley, 2011;Obaidalahe & Steils, 2018), engagement (Pap et al, 2017), satisfaction (Leko Šimić & Pap, 2019) and other factors affecting theatre attendance, Hager and Kopczynski Winkler (2012) warned that neither scholars nor managers can afford to underemphasize the value of demographics in predicting performing arts attendance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that older audiences (over 60) in the Czech Republic are the most frequent classic theatre attendees. The same situation exists in Croatia, and if this is related to the longterm trend of the decline of classic theatre audiences (Leko Šimić & Pap, 2020), it is clear that a detailed age segments analysis is needed. Moreover, although several newer studies have concentrated on motivational factors (Walmsley, 2011;Obaidalahe & Steils, 2018), engagement (Pap et al, 2017), satisfaction (Leko Šimić & Pap, 2019) and other factors affecting theatre attendance, Hager and Kopczynski Winkler (2012) warned that neither scholars nor managers can afford to underemphasize the value of demographics in predicting performing arts attendance.…”
Section: Introductionmentioning
confidence: 99%
“…up to the age of 35 and over 35, respectively) and theatre attendance frequency. The reason for such an approach was that previous studies in Croatia have been done separately on young and adult audiences (Leko Šimić & Pap, 2020), so it was found interesting to compare the two age-based segments; Secondly, the population of 35+ has already built its "cultural profile," and it is highly unlikely that it will change significantly, whereas young existing and potential audiences can be reached by adequate marketing strategies, and their attitudes and behavior are easier to change. Chytková, et al (2012) also confirmed that age is a significant criterion to segment audiences.…”
Section: Introductionmentioning
confidence: 99%